2017
DOI: 10.1080/10408398.2016.1206845
|View full text |Cite
|
Sign up to set email alerts
|

Trends in microbial control techniques for poultry products

Abstract: Fresh poultry meat and poultry products are highly perishable foods and high potential sources of human infection due to the presence of several foodborne pathogens. Focusing on the microbial control of poultry products, the food industry generally implements numerous preventive measures based on the Hazard Analysis and Critical Control Points (HACCP) food safety management system certification together with technological steps, such as refrigeration coupled to modified atmosphere packaging that are able to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 144 publications
0
14
0
Order By: Relevance
“…However, as we observed, a recent study from Vietnam reported that 39% of the ESC-R- Ec from chicken meat were also CST-R ( Yamaguchi et al, 2018 ). The observation that ∼40% of the ESC-R- Ec contaminating chicken meat in Laos and Vietnam is also CST-R is alarming and should drive the implementation, whenever possible, of Hazard Analysis and Critical Control Points concepts to avoid the spread of these pathogens through the food chain ( Silva et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, as we observed, a recent study from Vietnam reported that 39% of the ESC-R- Ec from chicken meat were also CST-R ( Yamaguchi et al, 2018 ). The observation that ∼40% of the ESC-R- Ec contaminating chicken meat in Laos and Vietnam is also CST-R is alarming and should drive the implementation, whenever possible, of Hazard Analysis and Critical Control Points concepts to avoid the spread of these pathogens through the food chain ( Silva et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…The testing approach concentrates on the statistical significance of the parameters for the variables specifying the following: the allocation of decision rights around process design and prototyping (for H1 ); the allocation of decision rights around the specific type of innovation (for H1 ), as both market forces and a European Union legislation ban has induced poultry companies and farmers to search for a substitute for antibiotic growth promoter (AGP), which has a mode of action that is not fully understood and uncertain (Silva et al , 2017); and transaction ( H2a ) and production cost ( H2b ) determinants.…”
Section: Empirical Analysismentioning
confidence: 99%
“…Bearing in mind current consumer needs for fresh or minimally processed, microbiologically safe and healthy foods of high quality, a concept called hurdle technology has been proposed. This approach is based on the careful combination of traditional and novel preservation methods called ‘hurdles’ in order to inhibit growth of microorganisms and other deterioration reactions [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. In this context, the possibility of combining chilled storage with other techniques in the context of the ‘hurdle technology’ like the direct addition of chemical preservatives or, preferably, natural antimicrobial compounds is extensively studied as an effective way to further prolong the shelf life of animal tissue [ 29 , 55 , 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%